Block of Counter-Regulation By Inhibition of Protein Synthesis Sensitizes Cancer Cells to IRE1a-Mediated Apoptosis Following Unfolded Protein Response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, Scott; Wendland, Kerstin; George, Rebekka; Petkovic, Srdjan; Mellenthin, Lisa; Emmerich, Charlotte; Lutzny-Geier, Gloria; Metzler, Markus; Mackensen, Andreas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Improved Pseudomonas exotoxin and Mertansine-based Duotoxins for the treatment of hematologic malignancies - Ammon, Anna-Maria; George, Rebekka; Mellenthin, Lisa; Mackensen, Andreas; Mueller, F. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Targeted Inhibition of Protein Biosynthesis sensitizes Cancer Cells to IRE1a-mediated Apoptosis as a Consequence of the unfolded protein response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, S.; Wendland, Kerstin; George, Rebekka; Petkovic, S.; Mellenthin, Lisa; Emmerich, C.; Lutzny-Geier, Gloria; Mackensen, Andreas; Metzler, Markus; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Targeted inhibition of protein synthesis renders cancer cells vulnerable to apoptosis by unfolded protein response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, Scott; Wendland, Kerstin; George, Rebekka; Petkovic, Srdjan; Mellenthin, Lisa; Emmerich, Charlotte; Lutzny-Geier, Gloria; Metzler, Markus; Mackensen, Andreas; et al. (Cell Death & Disease, 2023)
Cellular stress responses including the unfolded protein response (UPR) decide over the fate of an individual cell to ensure survival of the entire organism. During physiologic UPR counter-regulation, protective proteins are upregulated to prevent cell death. A similar strategy induces resistance to UPR in cancer. Therefore, we hypothesized that blocking protein synthesis following induction of UPR substantially enhances drug-induced apoptosis of malignant cells. In line, upregulation of the chaperone BiP was prevented by simultaneous arrest of protein synthesis in B cell malignancies. Cytotoxicity by immunotoxins—approved inhibitors of protein synthesis—was synergistically enhanced in combination with UPR-inducers in seven distinct hematologic and three solid tumor entities in vitro. Synergistic cell death depended on mitochondrial outer membrane permeabilization via BAK/BAX, which correlated with synergistic, IRE1α-dependent reduction of BID, accompanied by an additive fall of MCL-1. The strong synergy was reproduced in vivo against xenograft mouse models of mantle cell lymphoma, Burkitt’s lymphoma, and patient-derived acute lymphoblastic leukemia. In contrast, synergy was absent in blood cells of healthy donors suggesting a tumor-specific vulnerability. Together, these data support clinical evaluation of blocking stress response counter-regulation using inhibitors of protein synthesis as a novel therapeutic strategy.
CRIS-Team Scopus Importer:2023-09-08

Triton X-114 and Amine-Based Wash Strategy Reduces Lipopolysaccharides to FDA Limit and Achieves Purer, More Potent Recombinant Immunotoxin - George, Rebekka; Gsottberger, Franziska; Ammon, Anna-Maria; Wendland, Kerstin; Mellenthin, Lisa; Mackensen, Andreas; Müller, Fabian (Bioconjugate Chemistry, 2021)
Many proteins are still routinely expressed prokaryotically in Escherichia coli, some because they are toxic to eukaryotes. Immunotoxins, which are fusion proteins of a targeting moiety and a truncated Pseudomonas exotoxin A, kill target cells by arresting protein synthesis. Thus, immunotoxins must be expressed in E. coli. Proteins expressed in E. coli are contaminated by endotoxin (also called lipopolysaccharides (LPS)). LPS binds to toll-like receptors, inducing up to life-threatening systemic inflammation in mammals. Therefore, accepted LPS limits for therapeutics as well as for substances used in immunological studies in animals are very low. Here, we report the use of Triton X-114 and polyamine-based wash strategies, which only in combination achieved LPS-contamination well below FDA limits. Resulting LPS-reduced immunotoxins were purer and up to 2.4-fold more active in vitro. Increased activity was associated with a 2.4-fold increase in affinity on cell surface expressed target antigen. The combination method maintained enzymatic function, protein stability, and in vivo efficacy and was effective for Fab as well as dsFv formats. With some modifications, the principle of this novel combination may be applied to any chromatography-based purification process.
CRIS-Team Scopus Importer:2021-05-14